Representasi Perundungan dalam Film From The Ashes Karya Khalid Fahad (Kajian Semiotika Ferdinand De Saussure) - Nafilatul Azza, Nawal; Rohanda, Rohanda (Green Publisher Indonesia, 2025)
This study discusses the representation of bullying in the film From The Ashes by Khalid Fahad through Ferdinand de Saussure's semiotic approach. The focus of this study is how signs in the film, whether through visuals, dialogues, or other symbols, represent bullying and its impact on victims. Qualitative research methods are used to analyze the signs in the film, which consist of two main components: the signifier and the signified. The results of the analysis show that the film uses strong symbolism to depict the dynamics of bullying, including power relations, the powerlessness of victims, and the journey towards recovery. Visual elements such as color, lighting, and facial expressions function as signifiers that strengthen the emotional narrative, while dialogue and storyline form signifiers that convey meaning about bullying. This study contributes to a deeper understanding of how film media can be a reflective medium for social issues such as bullying, while also offering a new perspective in semiotic studies.